Gestión del talento humano y su incidencia en la calidad del servicio de la empresa importadora castro quevedo, año 2023 - Palacios Anchundia, Nelly Jacqueline (2025)
This research paper, entitled "Human Talent Management and Its Impact on the Service Quality of the Importadora Castro Quevedo Company, 2023," presents the following: Human talent is vitally important for the success of a company, enabling an appropriate organizational climate and increasing productivity. Importadora Castro is a company with over 30 years of experience in the market, dedicated to the import, distribution, and sale of white goods, technology, medical supplies, motorcycles, toys, and more. Its current problem lies in the quality of service, which has led to dissatisfied customers, errors in orders, and delivery delays. The primary objective is to evaluate human talent management and its impact on service quality, thereby gathering important data to address logistics issues, strengthen the organizational climate, and improve efficiency and service quality. The sample consisted of one human talent director, 45 internal employees, and 380 of the company's clients. Among the weaknesses identified is the lack of staff training, which directly impacts service quality and customer experience. A solution